The effect of lateral lifting tasks on hand grip and pinch strength measurements - Abdul Rahman, Azrul Azwan; Tan, Joe Yee; Ahmad, Nadiah; A Rahman, Muhamad Arfauz (International Islamic University Malaysia (IIUM), 2021)
In lateral material handling tasks, which is very common in industries, warehouse systems, and other sectors, the workers can lead to work-related musculoskeletal disorders (WMSDs) because of the task and work designs, especially in upper extremities. WMSDs in hand, wrist, and fingers cause workers to have health problems, in pain and uncomfortable, hence decrease their working productivity and efficiency. The workstations distances are one of the factors that might affect workers when they perform manual material handling laterally, which can lead to WMSDs in hands. Hence, there is a need to study the relationship between transfer distances with the hand grip and pinch strengths. An experiment was carried out with 30 male participants to identify the relationship of lateral transfer distances with the hand grip and pinch strengths. The results obtained from the experiment were further investigated and analysed by using repeated measure one-way MANOVA and graphs. The results had proved that in the distances of 1.0 m, 1.25 m and 1.5 m did not affect one’s hand grip and pinch strengths. But, the postures and movements were varied based on distances.